Drill rod and preparation method thereof

The drill pipe structure with a carbon-silicon co-diffusion layer and CrAlSiN layer enhances hardness and erosion resistance, addressing the limitations of titanium alloy pipes in complex oil and gas fields, offering improved durability and performance.

CN119194342AActive Publication Date: 2024-12-27CHINA NAT PETROLEUM CORP +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310759579.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-27
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

Titanium alloy drill pipes face issues of low erosion resistance and short service life due to low surface hardness, poor wear resistance, and high cost, limiting their application in complex oil and gas field environments.

Method used

A drill pipe structure featuring a carbon-silicon co-diffusion layer with a CrAlSiN erosion-resistant layer and a silicon-carbon strengthening layer, formed through plasma vapor deposition, to enhance hardness, wear resistance, and erosion resistance.

Benefits of technology

The drill pipe exhibits higher hardness, better wear resistance, and extended service life, with improved bonding strength and reduced interface stress, making it suitable for harsh oil and gas field conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194342A_ABST
    Figure CN119194342A_ABST
Patent Text Reader

Abstract

The invention provides a drill rod and a preparation method thereof. The drill rod comprises a drill rod pipe body, a female connector and a male connector which are connected with the drill rod pipe body, and a carbon-silicon co-permeation layer and an erosion-resistant layer which are sequentially arranged on the surface of the drill rod pipe body, and the erosion-resistant layer comprises a CrAlSiN layer. The drill rod with the structure has the advantages of higher hardness, better wear resistance and erosion resistance, long service life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil and gas field drilling tools, and in particular to a drill rod and a preparation method thereof. Background Art

[0002] Drill pipes are commonly used downhole tools in oil and gas field exploitation. As the actual working conditions of oil and gas field exploitation become more and more complex, oil and gas drill pipes face increasingly severe corrosive environments and corrosion risks. Titanium alloy drill pipes are one of the main drill pipes currently used in oil and gas fields due to their light weight, high specific strength and certain corrosion resistance. However, due to the shortcomings of titanium alloy drill pipes such as low surface hardness, poor wear resistance, unsatisfactory corrosion and erosion resistance, and high cost, it is still difficult to meet the requirements of actual applications in oil and gas fields.

[0003] At present, the preparation of metal coating on the surface of titanium alloy drill pipe is the main way to improve the wear and erosion resistance of titanium alloy drill pipe. The preparation technologies of corresponding metal coatings include micro-arc oxidation, laser cladding, vacuum evaporation, hot dip plating, etc. However, although the prepared metal coating has the advantages of high hardness, high film-base bonding strength, corrosion resistance, and wear resistance, its coating still has defects such as rough surface, loose and porous, and large friction coefficient, which leads to reduced erosion resistance and shortened service life of titanium alloy drill pipe, which seriously limits the application of titanium alloy drill pipe in the erosion environment of oil and gas fields. Summary of the invention

[0004] The main purpose of the present invention is to provide a drill rod and a preparation method thereof, so as to solve the problems of low erosion resistance and short service life of the existing drill rods.

[0005] In order to achieve the above-mentioned objectives, the present invention provides a drill pipe, including a drill pipe body, a female joint and a male joint connected to the drill pipe body, and a carbon-silicon co-diffusion layer and an erosion-resistant layer sequentially arranged on the surface of the drill pipe body, wherein the erosion-resistant layer includes a CrAlSiN layer.

[0006] Furthermore, the thickness of the erosion-resistant layer is 2-5 μm, and the thickness of the carbon-silicon co-diffusion layer is 100-300 μm.

[0007] Furthermore, the erosion-resistant layer includes: a stacked CrAlSiN layer, a silicon-diffused layer and a CrAlSi transition layer, and the CrAlSi transition layer is arranged on a side close to the carbon-silicon co-diffused layer.

[0008] Furthermore, the drill pipe further comprises a silicon-carbon strengthening layer, and the silicon-carbon strengthening layer is arranged on a surface of the erosion-resistant layer away from the carbon-silicon co-diffusion layer.

[0009] Furthermore, the thickness of the silicon carbon strengthening layer is 0.5-3 μm.

[0010] The second aspect of the present application also provides a method for preparing the above-mentioned drill pipe, which comprises: performing carbon-silicon co-diffusion treatment on the surface of the drill pipe body to form a carbon-silicon co-diffusion layer; and using plasma vapor deposition to deposit on the surface of the carbon-silicon co-diffusion layer to form an erosion-resistant layer containing a CrAlSiN layer.

[0011] Further, the deposition process includes: S1, under vacuum conditions, argon flow and SiH4 flow, a CrAl target material is used to perform a first deposition process on the drill pipe body to form a CrAlSi transition layer; S2, under vacuum conditions and argon flow and SiH4 flow, a siliconization treatment is performed on the surface of the CrAlSi transition layer to form a siliconized layer; and S3, under vacuum conditions, argon flow, SiH4 flow and N2 flow, a Cr target material, a CrAl target material and an AlSi target material are used to perform a second deposition treatment on the surface of the siliconized layer to form a CrAlSiN layer; and S1 to S3 are optionally repeated to obtain an erosion-resistant layer.

[0012] Further, in the first deposition process, the temperature of the reaction chamber is 150°C to 300°C, the argon flow rate is 900 to 1200 sccm, the vacuum degree is 2.2 Pa to 3 Pa, the target current is 130A to 160A, the substrate bias is -85V to -115V, and the deposition time is 30min to 50min; optionally, in the siliconization process, the temperature of the reaction chamber is 310°C to 400°C, the argon flow rate is 50sccm to 100sccm, the SiH4 gas flow rate is 200sccm to 500sccm, the vacuum degree is 1.1 to 1.5Pa, and the substrate is molten. The bottom bias voltage is -90V to -120V, and the siliconization time is 3min to 10min; optionally, the temperature of the reaction chamber is 310℃ to 400℃, the argon gas flow rate is 800sccm to 1200sccm, the N2 gas flow rate is 200sccm to 400sccm, the vacuum degree is 2.0Pa to 3Pa, the substrate bias voltage is -85V to -115V, the arc current of the Cr target is 20A to 40A, the arc current of the CrAl target is 70 to 100A, the arc current of the AlSi target is 60 to 90A, and the CrAlSiN layer is deposited for 40min to 70min.

[0013] Further, the carbon-silicon co-penetration treatment process includes: using a carbon source and a silicon source to permeate the drill pipe body to obtain a carbon-silicon co-penetration layer; preferably, the carbon source is selected from one or more of methane, ethane, propylene and acetylene; the silicon source is selected from one or more of silane, methyltrichlorosilane, silicon tetrachloride and tetramethylsilane. Preferably, the temperature of the carbon-silicon co-penetration treatment process is 400-500°C, and the co-penetration time is 30-90 minutes.

[0014] Furthermore, the preparation method of the drill pipe also includes: forming a silicon-carbon strengthening layer on the surface of the erosion-resistant layer away from the carbon-silicon co-diffusion layer by using a plasma enhanced chemical vapor deposition method.

[0015] By applying the technical solution of the present invention, a carbon-silicon co-diffusion layer is formed on the surface of the drill pipe body, which can improve and increase the hardness and strength of the drill pipe body. At the same time, the carbon-silicon co-diffusion layer as a transition layer can alleviate the mismatch of thermal expansion coefficients between the drill pipe body and the erosion-resistant layer, while reducing the interface stress and increasing the bonding strength between the erosion-resistant layer and the drill pipe body, thereby enhancing the erosion resistance of the drill pipe. Providing the CrAlSiN layer on the surface of the carbon-silicon co-diffusion layer is beneficial to significantly improving the hardness, wear resistance and erosion resistance of the titanium alloy drill pipe. In summary, the drill pipe having the above structure has the advantages of higher hardness, better wear resistance and erosion resistance, and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 A schematic structural diagram of a drill rod provided for a typical implementation of the present application.

[0018] Figure 2 A schematic structural diagram of a protective coating in a drill pipe provided in a preferred embodiment of the present application.

[0019] Figure 3 Surface morphology test diagram of the CrAlSiN erosion-resistant layer on the surface of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application.

[0020] Figure 4 This is a surface morphology test diagram of the SiC strengthening layer on the surface of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application.

[0021] Figure 5 This is a graph showing the hardness value test results of the erosion-resistant layer on the surface of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application.

[0022] Figure 6 This is a test diagram of the friction performance of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application.

[0023] Figure 7 This is a test diagram of the erosion resistance performance of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application.

[0024] The above drawings include the following reference numerals:

[0025] 10. Drill pipe body; 20. Female joint; 30. Male joint; 40. Carbon-silicon co-diffusion layer; 50. Erosion-resistant layer; 51. CrAlSiN layer; 52. Silicon-diffusion layer; 53. CrAlSi transition layer; 60. Silicon-carbon strengthening layer. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0027] As described in the background technology, the existing drill pipe has the problems of low erosion resistance and short service life. In order to solve the above technical problems, the present application provides a drill pipe, such as Figure 1 As shown, the drill pipe includes a drill pipe body 10, a female joint 20 and a male joint 30 connected to the drill pipe body 10, and a carbon-silicon co-diffusion layer 40 and an erosion-resistant layer 50 stacked in sequence on the surface of the drill pipe body 10, wherein the erosion-resistant layer 50 includes a CrAlSiN layer 51.

[0028] The formation of a carbon-silicon co-diffusion layer 40 on the surface of the drill pipe body 10 can improve and increase the hardness and strength of the drill pipe body 10. At the same time, the carbon-silicon co-diffusion layer 40 as a transition layer can alleviate the mismatch of thermal expansion coefficients between the drill pipe body 10 and the erosion-resistant layer 50, while reducing the interface stress and increasing the bonding strength between the erosion-resistant layer 50 and the drill pipe body 10, thereby enhancing the erosion resistance of the drill pipe. Providing the CrAlSiN layer 51 on the surface of the carbon-silicon co-diffusion layer 40 is beneficial to significantly improve the hardness, wear resistance and erosion resistance of the titanium alloy drill pipe. In summary, the drill pipe having the above structure has the advantages of higher hardness, better wear resistance and erosion resistance, and longer service life.

[0029] In a preferred embodiment, the thickness of the erosion-resistant layer 50 is 2-5 μm, and the thickness of the carbon-silicon co-infiltration layer 40 is 100-300 μm. The thickness of the erosion-resistant layer 50 and the carbon-silicon co-infiltration layer 40 includes but is not limited to the above ranges, and limiting them within the above ranges is beneficial to further improve the hardness and strength of the drill pipe and the erosion resistance, and is also beneficial to reduce the manufacturing cost.

[0030] In order to further improve the corrosion resistance and hardness of the drill pipe, in a preferred embodiment, the erosion-resistant layer 50 includes: a stacked CrAlSiN layer 51, a siliconized layer 52 and a CrAlSi transition layer 53, and the CrAlSi transition layer 53 is arranged on a side close to the carbon-silicon co-diffusion layer 40.

[0031] In a preferred embodiment, Figure 1As shown, the drill pipe also includes a silicon-carbon strengthening layer 60, which is arranged on the surface of the erosion-resistant layer 50 away from the carbon-silicon co-diffusion layer 40. The silicon-carbon strengthening layer 60 is prepared on the surface of the erosion-resistant layer 50, and the silicon-carbon strengthening layer 60 can not only further seal the micropores on the surface of the CrAlSiN layer 51, but also further improve the overall hardness and density of the erosion-resistant layer 50, thereby improving the overall performance of the drill pipe. More preferably, the thickness of the silicon-carbon strengthening layer 60 is 0.5 to 3 μm.

[0032] Figure 1 In the embodiment, the carbon-silicon co-diffusion layer 40, the erosion-resistant layer 50 and the silicon-carbon strengthening layer 60 are collectively referred to as the protective coating. Preferably, the hardness of the protective coating on the surface of the drill pipe is 40 to 53 GPa, the friction coefficient is 0.10 to 0.35, and the average erosion rate is 1.5 to 4.8×10 -9 Kg / m 2 ·s.

[0033] The second aspect of the present application also provides a method for preparing the above-mentioned drill pipe, the method for preparing the drill pipe comprising: performing carbon-silicon co-diffusion treatment on the surface of the drill pipe body 10 to form a carbon-silicon co-diffusion layer 40; using plasma vapor deposition to deposit on the surface of the carbon-silicon co-diffusion layer 40 to form an erosion-resistant layer 50 containing a CrAlSiN layer 51. The above-mentioned preparation method is simple, easy to operate, and has low cost. The drill pipe obtained has the advantages of high hardness, good wear resistance and erosion resistance, and long service life.

[0034] The carbon-silicon co-infiltration layer 40 can be formed in a conventional manner in the art. For example, the drill pipe body 10 is infiltrated with a carbon source and a silicon source to obtain the carbon-silicon co-infiltration layer 40; wherein the carbon source includes but is not limited to one or more of methane, ethane, propylene and acetylene; and the silicon source includes but is not limited to one or more of silane, methyltrichlorosilane, silicon tetrachloride and tetramethylsilane.

[0035] The provision of the carbon-silicon co-diffusion layer 40 can enhance the surface hardness of the drill pipe body and achieve matching of the thermal expansion coefficient with the erosion-resistant layer 50, so as to reduce the interface stress and enhance the bonding strength between the drill pipe body 10 and the erosion-resistant layer 50. In order to further increase the depth of siliconization, preferably, the temperature of the carbon-silicon co-diffusion treatment process is 400-500°C and the co-diffusion time is 30-90 minutes.

[0036] In a preferred embodiment, the above deposition process includes:

[0037] S1, in a vacuum condition, in an argon gas flow and a SiH4 gas flow, a first deposition process is performed on the drill pipe body 10 using a CrAl target material to form a CrAlSi transition layer 53;

[0038] S2, in a vacuum condition, in an argon flow and a SiH4 flow, performing siliconization treatment on the surface of the CrAlSi transition layer 53 to form a siliconized layer 52; and

[0039] S3, under vacuum conditions, argon flow, SiH4 flow and N2 flow, use Cr target, CrAl target and AlSi target to perform a second deposition treatment on the surface of the siliconized layer 52 to form a CrAlSiN layer 51; and optionally repeat S1 to S3 to obtain an erosion-resistant layer 50.

[0040] In order to further improve the corrosion resistance and strength of the erosion-resistant layer 50, the process in each step can be optimized. In a preferred embodiment, in the first deposition process, the temperature of the reaction chamber is 150°C to 300°C, the argon gas flow rate is 900 to 1200 sccm, the vacuum degree is 2.2Pa to 3Pa, the target current is 130A to 160A, the substrate bias is -85V to -115V, and the deposition time is 30min to 50min;

[0041] Optionally, during the siliconizing treatment, the temperature of the reaction chamber is 310° C. to 400° C., the argon gas flow rate is 50 sccm to 100 sccm, the SiH4 gas flow rate is 200 sccm to 500 sccm, the vacuum degree is 1.1 to 1.5 Pa, the substrate bias voltage is -90 V to -120 V, and the siliconizing time is 3 min to 10 min;

[0042] Optionally, during the second deposition process, the temperature of the reaction chamber is 310°C to 400°C, the argon gas flow rate is 800sccm to 1200sccm, the N2 gas flow rate is 200sccm to 400sccm, the vacuum degree is 2.0Pa to 3Pa, the substrate bias is -85V to -115V, the arc current of the Cr target is 20A to 40A, the arc current of the CrAl target is 70 to 100A, the arc current of the AlSi target is 60 to 90A, and the CrAlSiN layer is deposited for 40min to 70min.

[0043] In order to prevent the impurity elements from affecting the carbon-silicon co-penetration treatment, preferably, before the carbon-silicon co-penetration treatment, the preparation method of the drill pipe includes: using plasma to clean the drill pipe body 10 under vacuum conditions. Preferably, the plasma is argon plasma. The cleaning liquid includes but is not limited to one or more of alcohol, acetone and deionized water.

[0044] In a preferred embodiment, the process of depositing the CrAlSiN layer 51 on the carbon-silicon co-diffusion layer 40 further includes: a step of activating the target material, specifically, loading the cleaned drill pipe substrate, Cr target, CrAl target, and AlSi alloy target into the reaction chamber of the plasma vapor deposition equipment, and then evacuating the reaction chamber to 10-4 -10 - 8 Pa; the mass purity of the Cr target, CrAl target and AlSi alloy is not less than 99.9%; then the reaction chamber containing the target material and the substrate in S2 is heated to a temperature of 150°C to 300°C, and after heating to 150°C to 300°C, it is kept warm for 1min to 5min; while keeping warm, Ar gas is introduced until the vacuum degree of the reaction chamber is 1Pa to 2Pa, the Ar flow rate is 500sccm to 800sccm, and the purity of argon is not less than 99.999%; then the Cr target, CrAl target and AlSi alloy target are opened in turn for activation, the activation target current is 70A to 90A, and the activation time is 3 to 8min.

[0045] In order to further improve the cleanliness of the drill pipe surface, preferably, the surface of the cleaned drill pipe body 10 is bombarded and cleaned. Specifically, the temperature of the reaction chamber is maintained at 150°C to 300°C, the flow rate of Ar gas is increased to 900sccm to 1200sccm, and the vacuum degree of the reaction chamber is increased to 1.6Pa to 2.2Pa; then, the substrate (drill pipe body 10) is biased to -900V to -1100V to form Ar plasma, and the substrate is bombarded and cleaned for 6min to 12min to remove impurities on the substrate surface.

[0046] In a preferred embodiment, the method for preparing the drill pipe further comprises: forming a silicon-carbon strengthening layer 60 on a surface of the erosion-resistant layer 50 away from the carbon-silicon co-diffusion layer 40 by using a plasma enhanced chemical vapor deposition method.

[0047] The specific steps include:

[0048] (1) Place the drill pipe with the carbon-silicon co-diffusion layer 40 and the erosion-resistant layer 50 into the reaction chamber of the plasma vapor deposition equipment, and then evacuate the reaction chamber to 10 -5 ~10 -7 Pa.

[0049] (2) Load the Cr target, CrAl target, and AlSi alloy target into the reaction chamber of the plasma vapor deposition equipment, and then evacuate the reaction chamber to 10 -4 ~10 -8 Pa.

[0050] (3) Maintain the reaction chamber temperature at 100°C to 200°C, introduce a CH4 gas flow rate of 900 to 1200 sccm, introduce a SiH4 gas flow rate of 50 to 200 sccm, increase the reaction chamber vacuum to 2.5 Pa to 3.5 Pa, and adjust the substrate bias to -95 V to -125 V to prepare a silicon-carbon strengthening layer 60 for 0.5 h to 3 h.

[0051] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0052] Example 1

[0053] A erosion-resistant titanium alloy drill pipe comprises: a drill pipe body 10, a female joint 20 and a male joint 30 connected to the drill pipe body 10, and a carbon-silicon co-diffusion layer 40, an erosion-resistant layer 50 and a silicon-carbon strengthening layer 60 which are sequentially stacked on the surface of the drill pipe body 10, wherein the erosion-resistant layer 50 comprises a CrAlSiN layer 51, a siliconized layer 52 and a CrAlSi transition layer 53.

[0054] The specific preparation method is as follows:

[0055] (1) Place the drill pipe body 10 into the vacuum chamber and use a vacuum pump to evacuate the chamber to a vacuum degree of 10 - 4 Pa; then a certain amount of argon is introduced, and a high-frequency pulse voltage is applied to form a high-energy argon plasma to clean the surface of the drill pipe body 10 for 30 minutes.

[0056] (2) Formation of carbon-silicon co-penetration layer 40: After cleaning, a certain amount of SiH4 and C2H2 are introduced to perform C-Si co-penetration on the surface of the drill pipe body 10 by low-temperature plasma technology. The co-penetration temperature is 430° C. and the C-Si co-penetration time is 45 minutes.

[0057] (3) Formation of the erosion-resistant layer 50:

[0058] S1, cleaning the substrate (drill pipe body 10 containing carbon-silicon co-diffusion layer 40), the cleaning liquid is acetone and deionized water, the volume ratio is 1:5;

[0059] S2, the cleaned substrate, Cr target, CrAl target, and AlSi alloy target obtained in S1 are placed in the reaction chamber of the plasma vapor deposition equipment, and then the reaction chamber is evacuated to 10 -8 Pa; the mass purity of Cr target, CrAl target and AlSi alloy is 99.99%;

[0060] S3, heating the reaction chamber containing the target material and the substrate in S2, the heating temperature is 230°C, heating to 200°C and then keeping the temperature for 5 minutes; while keeping the temperature, introducing argon gas until the vacuum degree of the reaction chamber is 1.5Pa, the argon gas flow rate is 600sccm, and the argon gas purity is 99.999%; then opening the Cr target, CrAl target, and AlSi alloy target in turn for activation, the activation target current is 85A, and the activation time is 6 minutes;

[0061] S4, performing plasma bombardment cleaning treatment on the surface of the substrate in S3, the specific process is: maintaining the temperature of the reaction chamber at 230° C., increasing the flow rate of argon gas to 1100 sccm, and increasing the vacuum degree of the reaction chamber to 2 Pa; then loading the substrate with a bias voltage of -1020 V to form argon plasma, and bombarding and cleaning the substrate for 10 minutes to remove impurities on the substrate surface;

[0062] S5, preparing a CrAlSi transition layer 53 on the surface of the substrate cleaned in S4, the specific process is: maintaining the temperature of the reaction chamber at 230° C., changing the argon gas flow rate to 1050 sccm, and introducing SiH4 gas at a flow rate of 150 sccm to increase the vacuum degree of the reaction chamber to 2.6 Pa, turning on the CrAl target and adjusting the target current to 145 A, and adjusting the substrate bias voltage to -105 V, depositing CrAlSi for 40 minutes, and forming the desired CrAlSi transition layer 53;

[0063] S6, the CrAlSi transition layer prepared in S5 is subjected to Si infiltration treatment to prepare a silicon infiltrated layer 52, and the specific process is: further heating the reaction chamber to increase the reaction chamber temperature to 340° C.; adjusting the argon gas flow rate to 75 sccm, and the SiH4 gas flow rate to 300 sccm; adjusting the vacuum degree of the reaction chamber to 1.2 Pa; adjusting the substrate bias voltage to -100 V, and the Si infiltration treatment time to 8 minutes, to form the desired silicon infiltrated layer 52;

[0064] S7, preparing a CrAlSiN layer 51 on the surface of the CrAlSi transition layer after Si infiltration treatment in S6, the specific process is as follows:

[0065] Raise the temperature of the reaction chamber to 380°C, adjust the argon gas flow rate to 1000 sccm, and adjust the SiH4 gas flow rate to 500 sccm;

[0066] The N2 gas flow rate is adjusted to 300 sccm, the vacuum degree is adjusted to 2.5 Pa, the substrate bias voltage is adjusted to -105 V, the Cr target, the CrAl target, and the AlSi target are turned on, wherein the arc current of the Cr target is 35 A, the arc current of the CrAl target is 85 A, and the arc current of the AlSi target is 80 A, and CrAlSiN is deposited for 60 minutes to form the desired CrAlSiN layer 51;

[0067] S8. Repeat S5, S6 and S7 for 6 times in total to obtain the erosion-resistant layer 50.

[0068] (4) Forming the silicon-carbon strengthening layer 60, the specific process is as follows:

[0069] S1, placing the drill pipe obtained in step (3) into the reaction chamber of the plasma vapor deposition equipment, and then passing a vacuum pump

[0070] The reaction chamber is evacuated to 10 -5 ~10 -7 Pa;

[0071] S2, the titanium alloy drill rod, Cr target, CrAl target and AlSi alloy target obtained in N1 are loaded into the plasma vapor deposition

[0072] The reaction chamber of the equipment is then evacuated to 10 -4 ~10 -8 Pa;

[0073] S3. Under N2 atmosphere, a SiC strengthening layer is prepared on the surface of the titanium alloy drill pipe. The process of preparing the SiC strengthening layer is as follows: maintain the temperature of the reaction chamber at 100℃~200℃, introduce a CH4 gas flow rate of 900~1200sccm, introduce a SiH4 gas flow rate of 50~200sccm, increase the vacuum degree of the reaction chamber to 2.5Pa~3.5Pa, and adjust the substrate bias to -95V~-125V, and prepare the SiC strengthening layer for 0.5h~3h.

[0074] After step (4) is completed, the drill pipe body is connected to the titanium alloy female connector 20 through threads, and the right end is connected to the titanium alloy male connector 30 through threads, and finally the erosion-resistant titanium alloy drill pipe is obtained.

[0075] Performance Testing:

[0076] Figure 3 This is a surface morphology test diagram of the CrAlSiN layer 51 in the erosion-resistant layer 50 on the surface of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application. Figure 3 It can be seen that the grains of the CrAlSiN layer 51 in the erosion-resistant layer 50 on the surface of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 are tightly combined, and the coating has a high density.

[0077] Figure 4 This is a surface morphology test diagram of the silicon-carbon strengthening layer 60 on the surface of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application. Figure 4 It can be seen that the silicon-carbon strengthening layer 60 on the surface of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 has tightly bonded grains in the middle layer and a high coating density.

[0078] Figure 5 This is a graph showing the hardness test results of the erosion-resistant layer 50 on the surface of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 of the present application. Figure 5 It can be seen that the hardness value of the erosion-resistant layer 50 on the surface of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 is 53 GPa.

[0079] Figure 6 This is a test diagram of the friction performance of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application. Figure 6 It can be seen that the average friction coefficient of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 is 0.10.

[0080] Figure 7 This is a test diagram of the erosion resistance performance of the erosion-resistant titanium alloy drill pipe body prepared in Example 1 of the present application. Figure 7 It can be seen that

[0081] The average erosion rate of the erosion-resistant layer 50 on the surface of the erosion-resistant titanium alloy drill pipe body obtained in Example 1 is 1.5×10 -9 Kg / m 2

[0082] ·s.

[0083] Example 2

[0084] The preparation method is the same as that of Example 1, except that in step (1), the high-energy plasma cleaning time is 10 minutes.

[0085] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 50 GPa; the friction coefficient is 0.14; the average erosion rate is 2.2×10 -9 Kg / m 2 ·s.

[0086] Example 3

[0087] The preparation method is the same as that of Example 1, except that in step (2), the preparation temperature of the carbon-silicon co-diffusion layer 40 is 400°C.

[0088] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 48 GPa; the friction coefficient is 0.15; the average erosion rate is 2.5×10 -9 Kg / m 2 ·s.

[0089] Example 4

[0090] The preparation method is the same as that of Example 1, except that in step (2), the preparation temperature of the carbon-silicon co-diffusion layer 40 is 500°C.

[0091] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 46 GPa; the friction coefficient is 0.17; the average erosion rate is 2.9×10 -9 Kg / m 2 ·s.

[0092] Example 5

[0093] The preparation method is the same as that of Example 1, except that in step (2), the preparation time of the carbon-silicon co-diffusion layer 40 is 30 minutes.

[0094] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 47GPa; the friction coefficient is 0.14; the average erosion rate is 2.8×10 -9 Kg / m 2 ·s.

[0095] Example 6

[0096] The preparation method is the same as that of Example 1, except that in step (2), the preparation time of the carbon-silicon co-diffusion layer 40 is 90 minutes.

[0097] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 42GPa; the friction coefficient is 0.15; the average erosion rate is 3.5×10 -9 Kg / m 2 ·s.

[0098] Example 7

[0099] The preparation method is the same as that of Example 1, except that in step (2), the carbon source for carburizing is methane.

[0100] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 50 GPa; the friction coefficient is 0.15; the average erosion rate is 2.4×10 -9 Kg / m 2 ·s.

[0101] Example 8

[0102] The preparation method is the same as that of Example 1, except that in step (2), the silicon source for siliconization is tetramethylsilane.

[0103] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 42GPa; the friction coefficient is 0.28; the average erosion rate is 3.2×10 -9 Kg / m 2 ·s.

[0104] Example 9

[0105] The preparation method is the same as that of Example 1, except that during the preparation of the CrAlSiN layer 51, the deposition temperature is 300°C.

[0106] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 40 GPa; the friction coefficient is 0.35; the average erosion rate is 4.8×10 -9 Kg / m 2 ·s.

[0107] Example 10

[0108] The preparation method is the same as that in Example 1, except that during the preparation of the CrAlSiN layer 51, the deposition temperature is 450°C.

[0109] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 48 GPa; the friction coefficient is 0.25; the average erosion rate is 2.1×10 -9 Kg / m 2 ·s.

[0110] Embodiment 11

[0111] The preparation method is the same as that of Example 1, except that during the preparation of the CrAlSiN layer 51, the deposition time is 30 minutes.

[0112] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 51 GPa; the friction coefficient is 0.14; the average erosion rate is 1.8×10 -9 Kg / m 2 ·s.

[0113] Example 12

[0114] The preparation method is the same as that of Example 1, except that during the preparation of the CrAlSiN layer 51, the deposition time is 90 minutes.

[0115] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 46 GPa; the friction coefficient is 0.15; the average erosion rate is 2.0×10 -9 Kg / m 2 ·s.

[0116] Embodiment 13

[0117] The preparation method is the same as that of Example 1, except that during the preparation of the silicon-carbon strengthening layer 60 , the deposition temperature is 100° C.

[0118] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 51GPa; the friction coefficient is 0.13; the average erosion rate is 2.2×10 -9 Kg / m 2 ·s.

[0119] Embodiment 14

[0120] The preparation method is the same as that of Example 1, except that during the preparation of the silicon-carbon strengthening layer 60 , the deposition temperature is 200° C.

[0121] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 45GPa; the friction coefficient is 0.21; the average erosion rate is 2.5×10 -9 Kg / m 2 ·s.

[0122] Embodiment 15

[0123] The preparation method is the same as that of Example 1, except that during the preparation of the silicon-carbon strengthening layer 60 , the deposition time is 30 minutes.

[0124] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 47GPa; the friction coefficient is 0.18; the average erosion rate is 2.1×10 -9 Kg / m 2 ·s.

[0125] Example 16

[0126] The preparation method is the same as that of Example 1, except that during the preparation of the CrAlSiN layer 51, the deposition time is 3 hours.

[0127] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 48GPa; the friction coefficient is 0.16; the average erosion rate is 2.0×10 -9 Kg / m 2 ·s.

[0128] Embodiment 17

[0129] The preparation method is the same as that of Example 1, except that the erosion-resistant layer 50 does not include the CrAlSi transition layer 53 .

[0130] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 41GPa; the friction coefficient is 0.23; the average erosion rate is 3.3Kg / m 2 ·s.

[0131] Embodiment 18

[0132] The preparation method is the same as that of Example 1, except that the erosion-resistant layer 50 does not include the CrAlSi transition layer 53 and the siliconized layer 52 .

[0133] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 40GPa; the friction coefficient is 0.26; the average erosion rate is 3.9Kg / m 2 ·s.

[0134] Comparative Example 1

[0135] The preparation method is the same as that of Example 1, except that the erosion-resistant layer 50 is not provided.

[0136] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 21GPa; the friction coefficient is 0.52; the average erosion rate is 8.3Kg / m 2 ·s.

[0137] Comparative Example 2

[0138] The preparation method is the same as that of Example 1, except that the silicon-carbon strengthening layer 60 is not provided.

[0139] The results show that the hardness of the prepared erosion-resistant titanium alloy drill rod is 38GPa; the friction coefficient is 0.42; the average erosion rate is 6.1Kg / m 2 ·s.

[0140] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the formation of a carbon-silicon co-diffusion layer on the surface of the drill pipe body can improve and enhance the hardness and strength of the drill pipe body. At the same time, the carbon-silicon co-diffusion layer as a transition layer can alleviate the mismatch of thermal expansion coefficients between the drill pipe body and the erosion-resistant layer, while reducing the interface stress and improving the bonding strength between the erosion-resistant layer and the drill pipe body, thereby enhancing the erosion resistance of the drill pipe. Providing the CrAlSiN layer on the surface of the carbon-silicon co-diffusion layer is beneficial to significantly improve the hardness, wear resistance and erosion resistance of the titanium alloy drill pipe. In summary, the drill pipe having the above-mentioned structure has the advantages of higher hardness, better wear resistance and erosion resistance, and long service life.

[0141] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0142] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A drill pipe, characterized in that: The drill pipe comprises a drill pipe body (10), a female joint (20) and a male joint (30) connected to the drill pipe body (10), and a carbon-silicon co-diffusion layer (40) and an erosion-resistant layer (50) sequentially arranged on the surface of the drill pipe body (10), wherein the erosion-resistant layer (50) comprises a CrAlSiN layer (51).

2. The drill pipe according to claim 1, characterized in that: The thickness of the erosion-resistant layer (50) is 2 to 5 μm, and the thickness of the carbon-silicon co-diffusion layer (40) is 100 to 300 μm.

3. The drill pipe according to claim 1 or 2, characterized in that: The erosion-resistant layer (50) comprises: a CrAlSiN layer (51), a silicon-infiltrated layer (52), and a CrAlSi transition layer (53) which are stacked, and the CrAlSi transition layer (53) is arranged on a side close to the carbon-silicon co-infiltrated layer (40).

4. The drill pipe according to claim 3, characterized in that: The drill pipe further comprises a silicon-carbon strengthening layer (60), wherein the silicon-carbon strengthening layer (60) is arranged on a surface of the erosion-resistant layer (50) away from the carbon-silicon co-diffusion layer (40).

5. The drill pipe according to claim 4, characterized in that The thickness of the silicon-carbon strengthening layer (60) is 0.5-3 μm.

6. A method for preparing a drill pipe according to any one of claims 1 to 5, characterized in that: The preparation method of the drill pipe comprises: Carrying out a carbon-silicon co-diffusion treatment on the surface of the drill pipe body (10) to form a carbon-silicon co-diffusion layer (40); A plasma vapor deposition method is used to deposit on the surface of the carbon-silicon co-diffusion layer (40) to form an erosion-resistant layer (50) containing a CrAlSiN layer (51).

7. The method for preparing a drill pipe according to claim 6, characterized in that: The deposition process includes: S1, in a vacuum condition, an argon gas flow and a SiH4 gas flow, a CrAl target material is used to perform a first deposition process on the drill pipe body (10) to form a CrAlSi transition layer (53); S2, in a vacuum condition and in an argon flow and a SiH4 flow, performing siliconization treatment on the surface of the CrAlSi transition layer (53) to form a siliconized layer (52); and S3, under vacuum conditions, in an argon flow, a SiH4 flow and a N2 flow, a second deposition treatment is performed on the surface of the siliconized layer (52) using a Cr target, a CrAl target and an AlSi target to form a CrAlSiN layer (51); and optionally, S1 to S3 are repeated to obtain the erosion-resistant layer (50).

8. The method for preparing a drill pipe according to claim 7, characterized in that: In the first deposition process, the temperature of the reaction chamber is 150°C to 300°C, the argon flow rate is 900 to 1200 sccm, the vacuum degree is 2.2Pa to 3Pa, the target current is 130A to 160A, the substrate bias is -85V to -115V, and the deposition time is 30min to 50min; Optionally, during the siliconizing treatment process, the temperature of the reaction chamber is 310° C. to 400° C., the argon gas flow rate is 50 sccm to 100 sccm, the SiH4 gas flow rate is 200 sccm to 500 sccm, the vacuum degree is 1.1-1.5 Pa, the substrate bias voltage is -90 V to -120 V, and the siliconizing time is 3 min to 10 min; Optionally, the temperature of the reaction chamber is 310°C to 400°C, the argon gas flow rate is 800sccm to 1200sccm, the N2 gas flow rate is 200sccm to 400sccm, the vacuum degree is 2.0Pa to 3Pa, the substrate bias is -85V to -115V, the arc current of the Cr target is 20A to 40A, the arc current of the CrAl target is 70 to 100A, the arc current of the AlSi target is 60 to 90A, and the CrAlSiN layer is deposited for 40min to 70min.

9. The method for preparing a drill pipe according to claim 6, characterized in that: The carbon-silicon co-diffusion treatment process comprises: using a carbon source and a silicon source to perform a permeation treatment on the drill pipe body (10) to obtain the carbon-silicon co-diffusion layer (40); Preferably, the carbon source is selected from one or more of methane, ethane, propylene and acetylene; the silicon source is selected from one or more of silane, methyltrichlorosilane, silicon tetrachloride and tetramethylsilane; Preferably, the temperature of the carbon-silicon co-penetration process is 400-500° C., and the co-penetration time is 30-90 min.

10. The method for preparing a drill pipe according to claim 9, characterized in that: The method for preparing the drill pipe further comprises: forming a silicon-carbon strengthening layer (60) on a surface of the erosion-resistant layer (50) away from the carbon-silicon co-diffusion layer (40) by using a plasma enhanced chemical vapor deposition method.

Citation Information

Patent Citations

  • Coating layer structure of basic material of mold

    CN102817032A

  • Wear-resisting corrosion-resistant CrAlSiN composite coating and preparation method thereof

    CN105671499A

  • Composite coating for die-casting die and preparation method thereof

    CN108396292A

  • Anti-abrasion and anti-corrosion Cr / CrAlSiN composite coating and preparation method and application thereof

    CN108690983A

  • Microbit deposited with AlTiN coating, and preparation method thereof

    CN109023266A